Apoptosis Induction, a Sharp Edge of Berberine to Exert Anti-Cancer Effects, Focus on Breast, Lung, and Liver Cancer - Zhu, Yi; Xie, Na; Chai, Yilu; Nie, Yisen; Liu, Ke; Liu, Yufei; Yang, Yang; Su, Jinsong; Zhang, Chuantao (Frontiers in Pharmacology, 2022)
Cancer is the leading cause of death and one of the greatest barriers to increased life expectancy worldwide. Currently, chemotherapy with synthetic drugs remains one of the predominant ways for cancer treatment, which may lead to drug resistance and normal organ damage. Increasing researches have suggested that apoptosis, a type of programmed cell death, is a promising way for cancer therapy. Furthermore, natural products are important sources for finding new drugs with high availability, low cost and low toxicity. As a well-known isoquinoline alkaloid, accumulating evidence has revealed that berberine (BBR) exerts potential pro-apoptotic effects on multiple cancers, including breast, lung, liver, gastric, colorectal, pancreatic, and ovarian cancers. The related potential signal pathways are AMP-activated protein kinase, mitogen-activated protein kinase, and protein kinase B pathways. In this review, we provide a timely and comprehensive summary of the detailed molecular mechanisms of BBR in treating three types of cancer (breast, lung and liver cancer) by inducing apoptosis. Furthermore, we also discuss the existing challenges and strategies to improve BBR’s bioavailability. Hopefully, this review provides valuable information for the comprehension of BBR in treating three types of cancer and highlight the pro-apoptotic effects of BBR, which would be beneficial for the further development of this natural compound as an effective clinical drug for treating cancers.